Uptake patterns and predictors of colorectal cancer screening among adults resident in Spain: A population-based study from 2017 to 2020 - Silvia Portero de la Cruz; Jesús Cebrino (Frontiers Media S.A., 2023)
BackgroundAlthough population screening has improved the early diagnosis of colorectal cancer (CRC), most cases are diagnosed in symptomatic patients. This study aimed to estimate the prevalence and evolution over time of uptake patterns to fecal immunochemical test (FIT) as a screening test for CRC among individuals aged 50-69 in Spain, and to determine the predictive factors for uptake patterns to this type of screening based on sociodemographic, health, and lifestyle characteristics.MethodsA cross-sectional study with 14,163 individuals from the 2017 Spanish National Health Survey and the 2020 European Health Survey was performed, including as the main variable uptake pattern to FIT screening within the last 2 years, with which we analyzed sociodemographic factors, health status and lifestyle habits.Results38.01% of participants had undergone FIT in the previous 2 years, and from 2017 to 2020, a significant increase in the uptake rate for CRC was observed (2017: 32.35%, 2020: 43.92%, p < 0.001). The positive predictors to FIT uptake pattern included factors such as being between 57 and 69 years, having a higher educational level or a higher social class, having at least one chronic illness, frequent contact with the primary care physician, alcohol consumption and physical activity, while immigration and smoking habit were negative predictors.ConclusionIn Spain, although the evolution of FIT uptake pattern over time is positive, the prevalence of FIT uptake is still low (38.01%), not reaching the level considered as acceptable in the European guidelines. Moreover, there are disparities in CRC screening uptake among individuals.